2014
DOI: 10.1016/j.jtcvs.2014.07.029
|View full text |Cite
|
Sign up to set email alerts
|

Left ventricular dysfunction after mitral valve repair—the fallacy of “normal” preoperative myocardial function

Abstract: De novo postoperative LV dysfunction is not uncommon in patients with "normal" preoperative EF undergoing mitral valve repair. LV dysfunction can persist, impairing recovery of LV size, function, and survival. The consideration of mitral repair before the onset of excessive LV dilation or pulmonary hypertension, even in those with preserved EF, seems warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
94
2
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 110 publications
(103 citation statements)
references
References 31 publications
3
94
2
2
Order By: Relevance
“…This finding is consistent with previous study. 12 We do not consider that the postoperative reduction in LV ejection fraction and others express LV dysfunction caused by surgery. Preoperative ejection fraction or strain can be overestimated because of the presence of MR, and this overestimation disappears after surgery.…”
Section: Discussionmentioning
confidence: 98%
“…This finding is consistent with previous study. 12 We do not consider that the postoperative reduction in LV ejection fraction and others express LV dysfunction caused by surgery. Preoperative ejection fraction or strain can be overestimated because of the presence of MR, and this overestimation disappears after surgery.…”
Section: Discussionmentioning
confidence: 98%
“…49,50,[52][53][54][55][56] In the PARTNER (Placement of Aortic Transcatheter Valve) IA trial of a balloon-expandable valve, 50,53 TAVR (n=348) was noninferior to surgical AVR (n=351) for all-cause death at 30 days, 1 year, 2 years, and 5 years (P=0.001). 53,54 The risk of death at 5 years was 67.8% in the TAVR group, compared with 62.4% in the surgical AVR group (hazard ratio [HR]: 1.04, 95% confidence interval [CI]: 0.86 to 1.24; P=0. 76).…”
mentioning
confidence: 99%
“…Previous reports have shown that outcome after MV surgery is impaired once preoperative LVEF is <60%, and, thus, an LVEF <60% is considered abnormal and a potential indication for surgery in severe MR. 3 Additionally, impaired LVEF postoperatively (<50%) has been shown to predict poorer long-term survival. 9 All of these challenges in MR management have led to the recognition of a need for parameters other than LV size and LVEF that may assist in the detection of the approach or onset of LV dysfunction and help optimize surgical timing. Brain natriuretic peptide (BNP) is a hormone secreted from myocardial cells in response to either diastolic stretch indicating volume overload, or wall stress indicating pressure overload, and is a marker of LV dysfunction.…”
mentioning
confidence: 99%